Wnt Signalling in Regenerative Dentistry - Birjandi, Anahid A.; Sharpe, Paul (Frontiers in Dental Medicine, 2021)
Teeth are complex structures where a soft dental pulp tissue is enriched with nerves, vasculature and connective tissue and encased by the cushioning effect of dentin and the protection of a hard enamel in the crown and cementum in the root. Injuries such as trauma or caries can jeopardise these layers of protection and result in pulp exposure, inflammation and infection. Provision of most suitable materials for tooth repair upon injury has been the motivation of dentistry for many decades. Wnt signalling, an evolutionarily conserved pathway, plays key roles during pre- and post-natal development of many organs including the tooth. Mutations in the components of this pathway gives rise to various types of developmental tooth anomalies. Wnt signalling is also fundamental in the response of odontoblasts to injury and repair processes. The complexity of tooth structure has resulted in diverse studies looking at specific compartments or cell types of this organ. This review looks at the current advances in the field of tooth development and regeneration. The objective of the present review is to provide an updated vision on dental biomaterials research, focusing on their biological properties and interactions to act as evidence for their potential use in vital pulp treatment procedures. We discuss the outstanding questions and future directions to make this knowledge more translatable to the clinics.